Machado and Civic Virtue: From Literature to Life. - Fitz, Earl E. (Chasqui (01458973), 2022)
The author examines readers' and scholars' misunderstanding of Latin American writer Machado de Assis' literary works, which are commonly described as works that bulge with magical realism. Topics discussed include his argument that de Assis' works invite readers to put civic virtue into actions, the literary value of de Assis, and the undevalue of the interplay of literature and civic virtue.